Exploring Drought Responses in Mexican Soybeans: Plant Water Status, Shoot and Root Biomass, and Root System Architecture - Julio C. García‐Rodríguez; María K. Manzo‐Valencia; Víctor Olalde‐Portugal; Silvia E. Valdés‐Rodríguez (Food and Energy Security)
ABSTRACT Drought stress is the primary abiotic threat to soybean production. Drought tolerance mechanisms in Mexican soybeans have not yet been fully studied. We examined the responses of three Mexican soybean genotypes, with varying maturities, to progressive drought stress and recovery irrigation, regarding plant water status, biomass traits, root system architecture, and their relationships. Genotypes I1240, I700 (intermediate maturity), and E2309 (early maturity) were examined since they showed drought tolerance characteristics under field conditions in previous studies. Drought stress was applied at the R2 growth stage for 17 days, after that irrigation was restored. Control plants were irrigated normally throughout the study. Responses to severe drought stress were different depending on the genotype. Early genotype E2309 exhibited a wider root system and tolerated drought stress maintaining shoot biomass and root characteristics at a low plant water potential. Intermediate genotypes, I1240 and I700, avoided drought stress achieving a greater root system at a higher plant water potential. Due to drought, genotype I1240 showed a more prominent increase in root diameter; meanwhile, root biomass was not decreased in genotype I700. Genotype I700 displayed a longer root system with the highest root‐to‐shoot ratio and recovered root growth more efficiently after recovery irrigation. General effects also indicated a longer root system in this genotype. Therefore, it could be used as a genetic source to improve root traits to cope with drought. Morphological and biomass root traits are suitable for selecting drought stress–tolerant soybean genotypes.